Grafting Interiority: Generative Methodologies Between the Natural and the Synthetic - Abudayyeh, Rana (Interiority, 2021)
Design is approaching a crucial period where the exchange between interior and exterior systems needs to be rethought and addressed from the standpoint of resilience and innovative environmental responses. The era of the detached interior bubble that is climate controlled and therein severed from natural systems is no longer justified or feasible. Interior spaces must respond to environmental conditions and proactively engage natural systems. The paper examines grafting methodology as an interior spatial formula that aims to generate complex sectional strategies for new programmatic typologies. It showcases work from a third-year interior architecture studio where students utilised natural landscapes as the premise to develop generative computational models that informed their design interventions.While placing interior interventions between natural and synthetic processes, interior grafts outline a design tactic that challenges the disjunction between internal settings and external parameters. The potential to draw relevance from external parameters and integrate the derivative systems into the interior volume carries many implications for interior architecture and urban dynamics. This approach demarks a radical repositioning of the interior volume as a continuation of the exterior scape, proliferating a fluid and active interiority.